Non-pharmacological interventions to promote the sleep of patients after cardiac surgery: a systematic review - Fernanda de Souza Machado; Regina Claudia da Silva Souza; Vanessa Brito Poveda; Ana Lucia Siqueira Costa (Universidade de São Paulo, 2017)
ABSTRACT Objective: to analyze evidence available in the literature concerning non-pharmacological interventions that are effective to treat altered sleep patterns among patients who underwent cardiac surgery. Method: systematic review conducted in the National Library of Medicine-National Institutes of Health, Cochrane Central Register of Controlled Trials, Latin American and Caribbean Health Sciences Literature, Scopus, Embase, Cumulative Index to Nursing and Allied Health Literature and PsycINFO databases, and also grey literature. Results: ten controlled, randomized clinical trials were included in this review. Non-pharmacological interventions were grouped into three main categories, namely: relaxation techniques, devices or equipment to minimize sleep interruptions and/or induce sleep, and educational strategies. Significant improvement was found in the scores assessing sleep quality among studies testing interventions such as earplugs, sleeping masks, muscle relaxation, posture and relaxation training, white noise, and educational strategies. In regard to the studies' methodological quality, high quality studies as established by Jadad scoring were not found. Conclusion: significant improvement was found among the scores assessing sleep in the studies testing interventions such as earplugs, sleeping masks, muscle relaxation, posture and relaxation training, white noise and music, and educational strategies.